Pediatric epilepsy surgery in patients with Lennox-Gastaut syndrome after viral encephalitis - Liu, Qingzhu; Wu, Nan; Liu, Chang; Yu, Hao; Sun, Yu; Wang, Yao; Yu, Guojing; Wang, Shuang; Ji, Taoyun; Liu, Xiaoyan; Jiang, Yuwu; Cai, Lixin (Frontiers in Neurology, 2023)
Objective To analyse the surgical outcomes of pediatric patients with Lennox-Gastaut syndrome (LGS) secondary to viral encephalitis. Methods We retrospectively analyzed the data of four patients with LGS secondary to viral encephalitis who underwent surgery at the pediatric epilepsy center of Peking University First Hospital from January 2014 to December 2019. Preoperative evaluations included a detailed history, long-term video electroencephalography (VEEG), brain magnetic resonance imaging (MRI), positron emission tomography (PET) and a neuropsychological test. All patients were followed up at 1, 3, and 6 months and then yearly. The surgical outcome was evaluated according to the Engel classification. Results Among the four children, the surgeries were right temporo-parieto-occipital disconnection (case 1), corpus callosotomy (case 2), left temporo-parieto-occipital disconnection (case 3), and left temporal lobectomy (case 4). The pathology was gliosis secondary to viral encephalitis. The median follow-up time was 4 years (3–5 years). At the last follow-up, one case had Engel I, two cases had Engel III, and one case had Engel IV. Conclusions Preliminary observations shows that surgical treatment may be challenging for patients with LGS secondary to viral encephalitis. However, suitable surgical candidacy and approaches have a significant impact on the prognosis of the patients.